Continuous underground observation of the geomagnetic field in Xuzhou City, North China, and its time-varying characteristics - Han, Mei; Guo, Lianghui; Wang, Yun; Wang, Xiang (Frontiers in Earth Science, 2025)
Underground space in Xuzhou City, North China, has become a favorable site for continuous geomagnetic observation to reveal geomagnetic-field variations and to monitor seismic activity due to its distinct advantage of an “ultra-quiet” and “ultra-clean” environment with low electromagnetic interference. In order to evaluate the underground electromagnetic environment at the Longdong coal mine area (LCMA) in Xuzhou City and establish an underground geomagnetic observatory, we conducted a pilot experiment of continuous geomagnetic observations synchronously underground and on the ground during May 2023. In this experiment, two close-space fluxgate magnetometers were deployed in the underground roadway of the LCMA to observe the variations of geomagnetic three components simultaneously, and a proton magnetometer was installed on its ground to observe the variation of geomagnetic total field. Furthermore, we analyzed the features of the wavelet spectrum of these observed data, variation curves of the geomagnetic field, and coupling of the geomagnetic-field variations between underground and ground. In addition, we investigated the characteristics of different frequency bands and horizontal gradient of the underground geomagnetic variation. Our achievements are as follows: 1) the underground geomagnetic environment has the advantage of being stable and clean with a low level of background noise and thus is suitable for high-precision, long-term, and continuous observation of the geomagnetic field; 2) the variation of the geomagnetic field underground is well coupled with that on the ground, with minor differences primarily attributed to an induced magnetic field generated in the surrounding rocks by the external magnetic-field variation; 3) underground geomagnetic observation can clearly record rich time-varying information of the geomagnetic field including calm variation, magnetic storms, geomagnetic pulsations and so on. Moreover, the geomagnetic gradient field contains higher-resolution time-varying information than the conventional geomagnetic field. Our pilot experiment suggests favorable underground sites with low background noise at the LCMA and provides valuable references for understanding the spatiotemporal variation characteristics of geomagnetic field. Based on the findings of our pilot experiment, an underground geomagnetic observatory and calibration station will be established at the LCMA, enabling high-precision, continuous geomagnetic and electromagnetic observation experiments in the future. These efforts will provide crucial constraints for the study of the variation of the geomagnetic-field variation, as well as seismic activity monitoring and disaster early warning related to the Tan-Lu fault zone.